Burden among family caregivers of breast cancer patients in north coastal Andhra Pradesh: a hospital based cross-sectional study - Kajana, Venkata Phani Madhavi; Katta, Amaleswari; Bhimarasetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2020)
Background: A large number of patients with chronic diseases like cancer are cared for in homes by the family members. The vital role that these family members play as “caregivers” is well recognized. However, the burden on them is poorly understood. The objective of the study was to assess the caregiving burden among family caregivers of breast cancer patients and to explore the factors associated with high levels of caregiving burden among family members of breast cancer patients. Methods: A cross-sectional, hospital based study was conducted in a tertiary health care setting in Visakhapatnam A total of 45 primary caregivers who were accompanying the breast cancer patients to the Government Hospital were interviewed using Zarit burden interview. The socio demographic variables of the care givers like age, gender, occupation, income, relation with the patient were also obtained. Informed consent was obtained from the caregiver. Data analysis: Data was entered in the MS Excel spread sheet and it was analysed using SPSS software version 21.0. Results: The study population consisted of 26 (57.7%) males and 19 (42.3%) female caregivers. Very few 4 (9%) caregivers reported with no or mild burden during care giving. Majority 18 (40%) of the caregivers reported with mild to moderate burden, whereas 18 (40%) of the caregivers reported with moderate to severe burden. Few 5 (11%) reported with severe burden. Financial factors and uncertainty regarding the illness of the patient are associated with more burden. Conclusions: There is high burden among caregivers of cancer patients which should be addressed.